Witness against War: Researching the History of the Quake Peace Testimony - Roberts, Helen (Quaker studies, 2002)
This paper is intended as an aid to those researching the history of Quaker involvement in the peace movement in Britain. It surveys relevant primary sources in several key areas, namely records of the Society of Friends both nationally and in Yorkshire, personal papers of a sample of Yorkshire Quakers involved in peace work, and records of British peace associations. Both the historical context and a summary of the surviving sources are given for each collection surveyed, with details of where the material is held.